Reflections on Anni Albers’ writings: interactions between modern design and andean textiles (Revista de Ensino em Artes, Moda e Design, 2023)
This article looks at some of Anni Albers’ reflections on design and modern textile design theory – systematized in her writings throughout her trajectory in Bauhaus and Black Mountain College – in order to make considerations on three main themes within her work: the functionalist rhetoric, the centrality of materials in modern textile design and interactions between design and vernacular and traditional cultural forms. The article employs a literature review and research on museum collections, both physical and virtual, aiming to contribute to a critical thinking concerning the modern textile design, its historical development process and, mainly, its interactions with local cultures.
Keywords: textile design; modern design; design theory and critic